PRAKTIK-PRAKTIK MANAJEMEN SDM STRATEGIK: PENGUJIAN EMPIRIS UNIVERSALISTIK DAN KONTINJENSI DALAM MENJELASKAN KINERJA ORGANISASIONAL - Heru Kurnianto Tjahjono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2005)
There are several perspectives to explain the relationship between strategic humanresources management practices and organizational performance. This article discusses the controversy within each perspective, which is universalistic and contingency perspectives. This article tries to replicate some of Delerey and Doty’s research on modes of theorizing in strategic human resource management. Strategic human resource management practices are identified into seven practices and are used to develop argumentation from that individual perspective. Organizational performance is measured by financial performance. The results show that argumentations from those two perspectives can explain the variation levels within financial performance.Keywords: strategic HRM, universalistic, contingency, organizational performance